An open access mouse brain flatmap and upgraded rat and human brain flatmaps based on current reference atlases. Issue 3 (19th July 2020) - Hahn, Joel D.; Swanson, Larry W.; Bowman, Ian; Foster, Nicholas N.; Zingg, Brian; Bienkowski, Michael S.; Hintiryan, Houri; Dong, Hong‐Wei
Abstract: Here we present a flatmap of the mouse central nervous system (CNS) (brain) and substantially enhanced flatmaps of the rat and human brain. Also included are enhanced representations of nervous system white matter tracts, ganglia, and nerves, and an enhanced series of 10 flatmaps showing different stages of rat brain development. The adult mouse and rat brain flatmaps provide layered diagrammatic representation of CNS divisions, according to their arrangement in corresponding reference atlases: Brain Maps 4.0 (BM4, rat) (Swanson, The Journal of Comparative Neurology, 2018, 526, 935–943), and the first version of the Allen Reference Atlas (mouse) (Dong, The Allen reference atlas, (book + CD‐ROM): A digital color brain atlas of the C57BL/6J male mouse, 2007). To facilitate comparative analysis, both flatmaps are scaled equally, and the divisional hierarchy of gray matter follows a topographic arrangement used in BM4. Also included with the mouse and rat brain flatmaps are cerebral cortex atlas level contours based on the reference atlases, and direct graphical and tabular comparison of regional parcellation. To encourage use of the brain flatmaps, they were designed and organized, with supporting reference tables, for ease‐of‐use and to be amenable to computational applications. We demonstrate how they can be adapted to represent novel parcellations resulting from experimental data, and we provide a proof‐of‐concept for how they could form the basis of a web‐based graphical data viewer and analysis platform. The mouse, rat, and human brain flatmap vector graphics files (Adobe Reader/Acrobat viewable and Adobe Illustrator editable) and supporting tables are provided open access; they constitute a broadly applicable neuroscience toolbox resource for researchers seeking to map and perform comparative analysis of brain data. Abstract : The illustration shows several flatmap representations of the mammalian brain, selected and modified from a collection of new and enhanced flatmap representations of the mouse, rat, and human brain. The human brain flatmap primarily details cortical regionalization. The rat and mouse brain flatmaps are based on current brain reference atlases, and they represent all depths of the divisional hierarchy of central nervous system gray matter represented therein. Also represented for rat and mouse are white matter tracts, ganglia, and nerves, and for the rat a series of flatmaps illustrating stages of brain development. The rat and mouse brain flatmaps are designed to facilitate comparative analysis between these species, and for adaptability to novel parcellation schemas and computational applications. We give examples of these uses, including a proof‐of‐concept workflow demonstrating how the flatmaps could be adapted to form the basis of a web‐based graphical data viewer and analysis platform to represent a wide variety of brain data.